Danmarks nationalscene med skuespillere med funktionsvariationer - Schmidt-Larsen, Ida (Peripeti, 2022)
The article is based on a field study of Glad Teater (Glad Theatre): a theatre with a professional setting and a sheltered employment. The article discusses Glad Theatre’s understanding of inclusive performing arts and how they describe and create it. The article relates to the future of inclusive performing arts, according to Glad Theatre.